Discurso político e discurso da violência: uma análise sobre a interincompreensão polêmica nos tweets - França, Camila de Jesus (2022)
This work investigates the process of polemic inter-incomprehension in the production of political discourse, and the way a violent discourse can be developed from it. This research is affiliated with Discourse Analysis perspective, assuming as main basis the studies of Maingueneau (2008; 2010; 2015), and it is carried out within the scope of studies and research developed in the Research Group Reading and Production of Discourses (GLPPD-UFLA). The political factor has always been present in society, since it is part of the constitution of the (political) human being and leads him to modulate the use he makes of language, with the aim of persuading the others, for his own benefit or for the group of which he or she is a part. Thus, the constitution of this discourse has several faces and sides, and they are sometimes in opposite sides. In this way, it has been noticed that the political discourse is crossed by the discourse of violence, since the latter has contributed a lot to highlight the inter-incomprehension, which was already existing between the subjects. In order to carry out this study, we based ourselves on the ideas presented by Maingueneau (2008), according to which there is, within these discourses, the presence of features that make it possible to understand the polemic inter-incomprehension. We are also based on the analysis that investigates how this phenomenon results in the discourse of violence, carried out by Michaud (1989) and Odália (2012). Furthermore, studies on the Social-Historical Conditions of Discourse Production are taken into account, based on the works of Courtine (2014) and Orlandi (2015). The constituted corpus is part of the political discursive field and consists of posts from Twitter and a publication from the newspaper Folha de S.Paulo. We recognize that the way in which discourses are constituted can result in acts and states of violence, as this is part of the process of polemic incomprehension.